1982
DOI: 10.1159/000241590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Weight on Postnatal Development of the Proximal Small Intestine of the Rabbit

Abstract: The effect of oral intake and body weight on postnatal maturation of the small intestine was examined in infant rabbits with accelerated weight gain. Intestine from immature animals is characterized by large unidirectional Na fluxes, failure of Na absorption to respond to glucose but increased ability to absorb monosaccharides, and an enzyme pattern of high lactase and thymidine kinase and low sucrase. Postnatal development was monitored by measuring Na and glucose transport in short-circuited jejunum and enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Our previous findings [9] that nutrient intake and weight gain are important in initiating postnatal development of the small bowel may be related to growth itself and matura tion of the hypothalamus-pituitary-adrenal axis or to the release of another, yet unde fined, hormone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous findings [9] that nutrient intake and weight gain are important in initiating postnatal development of the small bowel may be related to growth itself and matura tion of the hypothalamus-pituitary-adrenal axis or to the release of another, yet unde fined, hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence exists that hormones play a role in the process of postnatal matu ration [1], The principle candidate for onto génie development of the intestine is cortico sterone [6][7][8], The physiologic trigger which activates the hormonal mechanism responsi ble for intestinal maturation, however, is not well understood. In a previous study, we demonstrated that oral nutrient intake and body weight, rather than chronologic age, were important in initiating postnatal devel opment of the intestine [9]. The biologic sig nal for ontogénie development appeared to be related to the quantity of nutrient intake and rate of growth.…”
Section: Introductionmentioning
confidence: 87%
“…The increased villus height may reflect increased cell proliferation and an advanced degree of intestinal maturity with more mature mucosal barrier function. In addition, increased enteral nutrient intake and accelerated weight gain also led to precocious maturation of the small intestinal epithelium, suggesting that the volume of food ingested and body weight also trigger maturation of the gastrointestinal tract [207].…”
Section: Protein Undernutrition and Nutritionally Regulated Hormonal mentioning
confidence: 99%
“…The physiologic mechanisms that control postnatal develop ment are not well understood, but nutrition appears to play an important role. In a pre vious study, we demonstrated that increased oral nutrient intake and accelerated weight gain induced precocious ontogénie develop ment of the intestine [6], The effect of thera peutic nutritional manipulations, which may have important consequences on the imma ture gastrointestinal tract, has not been ex tensively studied. Total parenteral nutrition (TPN) and intragastric infusion of synthetic formulae are frequently employed in the managment of young infants.…”
Section: Introductionmentioning
confidence: 96%